A multiplexed chip-based assay system for investigating the functional development of human skeletal myotubes in vitro - Smith, A.S.T.; Long, C.J.; Pirozzi, K.; Najjar, S.; McAleer, C.; Vandenburgh, H.H.; Hickman, J.J. (Journal of biotechnology, 2014)
•An assay for measuring functional performance of human muscle fibers was developed.•The system provides multiple data points per chip in defined serum-free conditions.•The collected data characterizes the maturation of human muscle cells in vitro.•This system may prove useful for future pre-clinical drug studies.•This is the first chip-based assay for drug discovery using human skeletal muscle. This report details the development of a non-invasive in vitro assay system for investigating the functional maturation and performance of human skeletal myotubes. Data is presented demonstrating the survival and differentiation of human myotubes on microscale silicon cantilevers in a defined, serum-free system. These cultures can be stimulated electrically and the resulting contraction quantified using modified atomic force microscopy technology. This system provides a higher degree of sensitivity for investigating contractile waveforms than video-based analysis, and represents the first system capable of measuring the contractile activity of individual human muscle myotubes in a reliable, high-throughput and non-invasive manner. The development of such a technique is critical for the advancement of body-on-a-chip platforms toward application in pre-clinical drug development screens.